The Official Underground 2012 Doomsday Survival Handbook - Complied by Mumfrey, W. H. (Cincinnati, Ohio HOW Books, 2012)
Nuclear holocaust, super volcano, asteroid impact, mega tsunami, alien invasion, zombie outbreak? Will the world end with a whimper or a bang? However it goes, W.H. Mumfrey prepares everyone for what to expect when the world is ending, how to survive a litany of doomsday scenarios and how to rebuild the earth if you're one of the survivors. The book covers such essential topics as: Foraging for food; Looting 101; Barricades and fortifications for beginners; Retro-technologies; Dealing with cannibals; Mutant identification; Post-apocalyptic fashions; Renovating your subterranean hideout; Decoys and booby-traps for dummies; and, Dating after doomsday
Include Color Illustration and Index
Keywords: Survival